First-order and second-order optimality conditions for nonsmooth constrained problems via convolution smoothing - Eberhard, Andrew C.; Mordukhovich, Boris S. (Optimization, 2011)
This article mainly concerns deriving first-order and second-order necessary (and partly sufficient) optimality conditions for a general class of constrained optimization problems via smoothing regularization procedures based on infimal-like convolutions/envelopes. In this way, we obtain first-order optimality conditions of both lower subdifferential and upper subdifferential types and then second-order conditions of three kinds involving, respectively, generalized second-order directional derivatives, graphical derivatives of first-order subdifferentials and second-order subdifferentials defined via coderivatives of first-order constructions.